Numerical analysis of the solidity effect of a ducted, highly loaded, hovering UAM-vehicle engine - Nemo Juchmann and Dragan Kožulović and Tianxiang Hu and Rinie A. D. Akkermans (Aerospace science and technology, 2025)
The concept of future urban mobility often requires the integration of the third spatial dimension. Urban air mobility (UAM) vehicles are designed to provide such airborne transportation, and their design and operational planning must address both technical requirements and societal concerns, particularly regarding safety and noise. In this study, the impact of solidity on aerodynamic and aeroacoustic performance is examined. Beyond these considerations, the number of blades has been demonstrated to exert a substantial influence on the weight of the propulsion system. The present design, characterized by its relatively low aspect ratios, high solidity, and high blade loading, deviates from the majority of existing UAM-vehicle rotor designs, which feature comparatively thin, long rotors with low solidities. The analysis was conducted using both steady-state and transient 3D RANS simulations. To maintain a consistent thrust requirement, the rotational frequency was varied in one test series, while the stagger angle was adjusted in another. The study also considered the fundamental effects of core flow and sidewall interactions. Finally, tonal acoustic differences for selected test cases were compared using the FWH analogy. The results revealed that reducing solidity by one-third, relative to the reference case, led to a 2.17% increase in aerodynamic efficiency, accompanied by a moderate 1.4 dB rise in aeroacoustic load.
Keywords: UAM-Vehicle; UAV; Ducted Rotor-Stator; Effect of Solidity; Aeroacoustics